Dandyism : forming fiction from modernism to the present - Gutkin, Len, 1985- (Cultural frames, framing culture., 2020)
"This work traces the aesthetic of Victorian "dandies" from works such as Oscar Wilde's The Picture of Dorian Gray through the work of later twentieth-century American and British authors, including Ernest Hemingway, Raymond Chandler, William S. Burroughs, and Djuna Barnes, as well as in postmodern thrillers, providing a revisionist history of the relationship between Victorian aesthetics and twentieth-century literature"--